2018
DOI: 10.1158/1535-7163.mct-17-0927
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Suppresses Tumor Progression by Inactivating Stromal Fibroblasts in Ovarian Cancer

Abstract: Ovarian cancer is a devastating disease due to its high incidence of relapse and chemoresistance. The tumor microenvironment, especially the tumor stroma compartment, was proven to contribute tremendously to the unsatisfactory chemotherapeutic efficacy in ovarian cancer. Cytotoxic agents not only effect tumor cells, but also modulate the phenotype and characteristics of the vast stromal cell population, which can in turn alter the tumor cell response to chemointervention. In this study, we focused on the tumor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 68 publications
3
49
1
1
Order By: Relevance
“…Another idea is to reprogram CAFs back to a quiescent phenotype by inhibiting activating pathways, e.g., nuclear factor kappa B (NFκb) signaling that is increased in activated fibroblasts. Inhibition of NFκb reversed the typical CAF phenotype and improved response to cisplatin in ovarian cancer xenografts (Xu et al, 2018). The authors also showed that NFκb inhibition strongly reduced the deposition of collagen in the tumor matrix observed after cisplatin treatment.…”
Section: Carcinoma-associated Fibroblastsmentioning
confidence: 87%
See 1 more Smart Citation
“…Another idea is to reprogram CAFs back to a quiescent phenotype by inhibiting activating pathways, e.g., nuclear factor kappa B (NFκb) signaling that is increased in activated fibroblasts. Inhibition of NFκb reversed the typical CAF phenotype and improved response to cisplatin in ovarian cancer xenografts (Xu et al, 2018). The authors also showed that NFκb inhibition strongly reduced the deposition of collagen in the tumor matrix observed after cisplatin treatment.…”
Section: Carcinoma-associated Fibroblastsmentioning
confidence: 87%
“…CAFs already contribute to chemoresistance by themselves via various mechanisms: PAI-1, a cytokine produced by CAFs, activates Erk/Akt signaling and suppresses caspase-3 activation, which is necessary for tumor apoptosis following chemotherapeutic stress (Che et al, 2018). Similarly, interleukin 6 (IL6) is also produced predominantly by CAFs and induces expression of resistance-mediating CXCR7 in tumor cells (Qiao et al, 2018;Xu et al, 2018). Especially under hypoxic conditions, CAFs produce high levels of TGFβ, which induces stem celllike properties in tumor cells including increased resistance to chemotherapy (Tang et al, 2018).…”
Section: Carcinoma-associated Fibroblastsmentioning
confidence: 99%
“…Intriguingly, it was recently shown that breast cancer exosomes have enhanced pre-metastatic niche forming ability in the lung after a chemotherapy application [76]. In another study, researchers showed the first-line chemotherapeutic cisplatin to increase IL-6-producing myofibroblastic CAFs in ovarian cancer patients by activating the NFκB signaling pathway [77]. Furthermore, they demonstrated pretreatment with the well-known diabetes drug metformin arrested stromal NFκB/IL6 activation and lessened the chemoresistance response in ovarian cancer cells [77].…”
Section: Exosome-educated Cells In the Pre-metastatic Niche Promote Mmentioning
confidence: 99%
“…In another study, researchers showed the first-line chemotherapeutic cisplatin to increase IL-6-producing myofibroblastic CAFs in ovarian cancer patients by activating the NFκB signaling pathway [77]. Furthermore, they demonstrated pretreatment with the well-known diabetes drug metformin arrested stromal NFκB/IL6 activation and lessened the chemoresistance response in ovarian cancer cells [77]. Metastatic and drug-resistant, recurrent ovarian cancer produces significantly higher IL-6 compared to matched primary tumors.…”
Section: Exosome-educated Cells In the Pre-metastatic Niche Promote Mmentioning
confidence: 99%
“…Thus, the association between metformin use and PDAC is controversial (Chaiteerakij et al, 2016). However, it should be emphasized that metformin has been proposed to have effects on cancer stem cells (CSC) and sensitivity to chemotherapy (Hirsch et al, 2009(Hirsch et al, , 2013Iliopoulos et al, 2011;Rattan et al, 2011;Bao et al, 2012Bao et al, , 2014Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%